Penggunaan Propolis sebagai Suplementasi Pakan Kucing di dalam Penampungan Guna Mempertahankan Bobot Tubuh dan Massa Otot - Andini Eva Sari; Ronny Lesmana; Aziiz Mardanarian (Faculty of Veterinary Medicine, Udayana University and Published in collaboration with the Indonesia Veterinarian Association, 2025)
Malnutrition cats in shelters due to lack of daily intake requirements are still a problem that owners must face. Balanced nutrition for cats will support their appearance and improve their life quality by lowering the risk of certain medical conditions. Propolis, one of supplementation to support health from natural products, has been studied due to its immunomodulatory activities. However, there are very limited studies about the benefit of propolis in cats as food supplementation. For this reason, this experiment was aimed to determine the benefit of propolis as a feed supplement for managing weight changes in cats in shelters. The experiment was designed descriptively and using a purposive sampling method. The cat samples used in the study amounted to six cats from the same shelter with female and male gender aged 2-3 months with an initial body weight of less than 1 kg. All malnourished samples were fed with kitten dry feed and homemade wet feed as the control group, and the treatment group was supplemented with 15% propolis 1 mL/day per oral. After 30 days of propolis administration, compared to the control group, the propolis group as individuals presented no weight loss, they tended to maintain the body weight. In addition, there was an increase in the fore limb of each individual in the propolis group each week. These findings indicate that propolis can be used to manage the body weight of cats if accompanied by a balanced diet intake.